2012
DOI: 10.3389/fpsyg.2012.00574
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Tune: Listeners Like Music that Expresses a Contrasting Emotion

Abstract: Theories of esthetic appreciation propose that (1) a stimulus is liked because it is expected or familiar, (2) a stimulus is liked most when it is neither too familiar nor too novel, or (3) a novel stimulus is liked because it elicits an intensified emotional response. We tested the third hypothesis by examining liking for music as a function of whether the emotion it expressed contrasted with the emotion expressed by music heard previously. Stimuli were 30-s happy- or sad-sounding excerpts from recordings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…As in many other studies (e.g. Hunter et al 2008Hunter et al , 2010Hunter et al , 2011aHunter et al , 2011bHusain et al 2002;Khalfa et al 2008;Ladinig and Schellenberg 2012;Schellenberg et al 2008;Thompson et al 2001;Vieillard et al 2008), these adult listeners initially preferred positively valenced over negatively valenced music. After repeated exposure to both types of music, however, responses became more polarized.…”
Section: Liking and Exposuresupporting
confidence: 73%
See 2 more Smart Citations
“…As in many other studies (e.g. Hunter et al 2008Hunter et al , 2010Hunter et al , 2011aHunter et al , 2011bHusain et al 2002;Khalfa et al 2008;Ladinig and Schellenberg 2012;Schellenberg et al 2008;Thompson et al 2001;Vieillard et al 2008), these adult listeners initially preferred positively valenced over negatively valenced music. After repeated exposure to both types of music, however, responses became more polarized.…”
Section: Liking and Exposuresupporting
confidence: 73%
“…Frequency of exposure may also affect liking differently across individuals, as a consequence of differences in personality or other variables. In one study, Hunter and Schellenberg (2011a) reanalysed the data from the focused listening conditions of two previously reported experiments (Schellenberg et al 2008;Szpunar et al 2004, Experiment 2). As a group, participants exhibited an inverted-U shaped pattern of liking as a function of exposure frequency, as reported in the original published articles.…”
Section: Liking and Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Some individuals report that their preference for sad music is dependent on the time of day when they listen (Taruffi and Koelsch, 2014 ). Other studies have shown that liking of sad music increases when the listener is repeatedly exposed to the musical excerpt while distracted or mentally fatigued (Schellenberg et al, 2008 ) or when the music is preceded by multiple happy-sounding excerpts (Schellenberg et al, 2012 ). Empirical evidence that context can have an effect on one’s emotional response to music was recently found in a study in which participants who listened to music alone showed greater skin conductance response compared to participants who listened to the same music in a group (Egermann et al, 2011 ).…”
Section: The Tragedy Paradox: Philosophical and Psychological Approacmentioning
confidence: 99%
“… Parker et al (2008) reported that musical pieces tend to be evaluated positively if they follow bad musical pieces (positive hedonic contrast), whereas musical pieces tend to be evaluated negatively if they follow good musical pieces (negative hedonic contrast). Schellenberg et al (2012) showed that emotional contrasts between adjacent musical stimuli intensify listeners’ emotional responses, and the intensified emotional responses tend to increase listeners’ appreciation because music evoking strong emotions is preferred by listeners. Notably, hedonic-contrast effects have been particularly associated with responses to stimuli that are evaluated esthetically ( Parducci, 1995 ; Dolese et al, 2005 ; Zellner et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%